TC-UV Reactors Evaluated as an Alternative Option in Treatment of Ballast Water - Elcicek, Huseyin; Guzel, Bulent (CHAMBER MARINE ENGINEERS, 2020)
Over the last decade, UV disinfection technology has been widely employed in the disinfection of non-native species in wastewater and process water treatment. In this study, we assessed the feasibility of the adoption of a Taylor-Couette UV reactor in disinfection of unwanted species commonly found in ballast water. With this purpose, glycerol solutions were used in a Taylor Couette reactor with two different radius ratios. The observed flow structures and the critical transition values were simultaneously compared with each other and literature. Emergent flow structures in TC reactors provide considerable improvement in axial and radial mixing of particles and increasing the efficiency of the disinfection of E. coli. The obtained results show the possibility of utilizing the Taylor-Couette UV reactors as an alternative method in inactivation of non-native species in the ballast water.
Keywords: Taylor Couette flow; Ballast water; UV disinfection; TAYLOR-COUETTE; DISINFECTION; WAVY; FLOW; FILTRATION; COLI; Engineering; Transportation